Modulation of Autophagy by a Small Molecule Inverse Agonist of ERRα Is Neuroprotective - Suresh, S. N.; Chavalmane, Aravinda K.; Pillai, Malini; Ammanathan, Veena; Vidyadhara, D. J.; Yarreiphang, Haorei; Rai, Shashank; Paul, Abhik; Clement, James P.; Alladi, Phalguni A.; Manjithaya, Ravi (Frontiers in Molecular Neuroscience, 2018)
Mechanistic insights into aggrephagy, a selective basal autophagy process to clear misfolded protein aggregates, are lacking. Here, we report and describe the role of Estrogen Related Receptor α (ERRα), new molecular player of aggrephagy, in keeping autophagy flux in check by inhibiting autophagosome formation. A screen for small molecule modulators for aggrephagy identified ERRα inverse agonist XCT 790, that cleared α-synuclein aggregates in an autophagy dependent, but an MTOR independent manner. XCT 790 modulates autophagosome formation in an ERRα dependent manner as validated by siRNA mediated knockdown and over expression approaches. We show that, in a basal state, ERRα is localized on to the autophagosomes and upon autophagy induction by XCT 790, this localization is lost and is accompanied with an increase in autophagosome biogenesis. In a preclinical mouse model of Parkinson’s disease, XCT 790 exerted neuroprotective effects in the dopaminergic neurons of brain by inducing autophagy to clear toxic protein aggregates and in addition, ameliorated motor co-ordination deficits. Using a chemical biology approach, we unrevealed the role of ERRα in regulating autophagy and can be therapeutic target for neurodegeneration.